Factors of Stunting from Mother's Pregnancy to Toddler Under 59 Months-Old - Caesar Lagaliggo Givani (Indonesian Journal of Multidisciplinary Science, 2022)
Stunting is a chronic condition caused by malnutrition in the long term, causing stunted growth in children. Lack of nutritional intake in the long term will cause the growth of height in children to be shorter than the standard age. Factors that cause stunting in children include malnutrition during the mother's womb, genetic factors, lack of exclusive breastfeeding, infection factors, and the age of the baby. This study uses a literature study research method, while data collection techniques are carried out by exploring journals and other information relevant to the study. The results of this study indicate that the main factor that is the focus of research on the causes of stunting during pregnancy and after delivery is the condition of Low Birth Weight Babies (LBW) caused by lack of nutritional intake during childbirth, and the lack of optimal exclusive breastfeeding after childbirth.